Dynamic tensile behavior of novel quenching-partitioning-tempering martensitic steel. Issue 1 (3rd April 2019) - Hao, Qingguo; Qin, Shengwei; Liu, Yu; Zuo, Xunwei; Chen, Nailu; Rong, Yonghua
ABSTRACT: A Fe–0.20C–1.49Mn1.52Si–0.58Cr–0.05Nb low-carbon steel was treated by a novel quenching-partitioning-tempering (Q-P-T) process and the traditional quenching and tempering (Q&T) process for comparison, respectively. X-ray diffraction results indicate that there is 10.8% volume fraction of retained austenite ( V RA ) in the Q-P-T martensitic steel, while no diffraction peak of retained austenite was detected in Q&T martensitic steel. The Q-P-T steel and the Q&T steel were subjected to a dynamic tensile test at a strain rate of 500 s −1 and a quasi-static tensile test at a strain rate of 5.6 × 10 −4 s −1, respectively. The results indicate that the high strain rate in the dynamic tension raises the strength of the Q-P-T and Q&T steels compared with their quasi-static tensions owing to strain rate hardening effect, however, the elongation of Q-P-T steel decreases slightly, while the elongation of Q&T steel evidently increases. This difference is attributed that the existence of the dislocation absorption by the retained austenite (DARA) effect in quasi-static tension is suppressed under dynamic tensile loading so that the enhancement influence of DARA effect on ductility cannot be effectively compensated by the adiabatic softening of the martensitic matrix, which leads to a slight decrease in the elongation of the Q-P-T steel in dynamic tension compared with that in the quasi-static tension. While Q&T steel has no DARA effect in quasi-static tension due to no retained austenite, and thus the adiabatic softening of the martensitic matrix increases the ductility of Q&T steel in dynamic tension.